2022
DOI: 10.1177/23259671221128041
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Ulnar Collateral Ligament Reconstructions in Major League Baseball Pitchers: A Comparison of the “Tall and Fall” Versus “Drop and Drive” Pitching Styles

Abstract: Background: Previous pilot research has investigated differences in elbow valgus torque between the “tall and fall” (TF) and “drop and drive” (DD) pitching styles. Whether one of these pitching styles is associated with a greater rate of ulnar collateral ligament reconstruction (UCLR) is currently unknown. Purpose: To determine the proportion of Major League Baseball (MLB) pitchers using the TF and DD pitching styles who underwent UCLR over a 10-year period. Study Design: Cross-sectional study; Level of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…5,12,25 The prevalence of UCLR among MLB pitchers has increased in the past 15 years. 8 In a recent study, 3 we demonstrated that a higher proportion of UCL-injured MLB pitchers who underwent UCLR from 2007 to 2017 used the TF pitching style compared with the DD style (72.6% vs 27.4%, respectively). Nonetheless, it is unknown what proportion of MLB pitchers use the TF and DD pitching styles and whether either of these pitching styles elicits a greater rate of UE injury or UCLR.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…5,12,25 The prevalence of UCLR among MLB pitchers has increased in the past 15 years. 8 In a recent study, 3 we demonstrated that a higher proportion of UCL-injured MLB pitchers who underwent UCLR from 2007 to 2017 used the TF pitching style compared with the DD style (72.6% vs 27.4%, respectively). Nonetheless, it is unknown what proportion of MLB pitchers use the TF and DD pitching styles and whether either of these pitching styles elicits a greater rate of UE injury or UCLR.…”
mentioning
confidence: 83%
“…The procedural protocol used to distinguish the TF and DD pitching styles was adapted from our previous study. 3 The pitching style was assessed through the use of pitching videos attained from open media sources. Each video was collected from the 2019 athletic year.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations